2015
DOI: 10.1089/rej.2014.1650
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water-Based Training on Static and Dynamic Balance of Older Women

Abstract: The water-based training was effective in improving dynamic balance, but not static balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 36 publications
1
19
1
Order By: Relevance
“…Twelve of the sourced studies were randomized controlled trials (RCTs) [16, 24–34] and two studies adopted a quasi-experimental design [35, 36]. Nine studies specifically evaluated the impact of aquatic training on improving strength [16, 25, 27, 29–32, 35, 36], nine studies assessed balance following aquatic training [24, 26, 28–30, 32, 33, 35, 36], and four studies compared a variety of physical fitness components, including agility, endurance, flexibility and speed [26, 27, 35, 36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve of the sourced studies were randomized controlled trials (RCTs) [16, 24–34] and two studies adopted a quasi-experimental design [35, 36]. Nine studies specifically evaluated the impact of aquatic training on improving strength [16, 25, 27, 29–32, 35, 36], nine studies assessed balance following aquatic training [24, 26, 28–30, 32, 33, 35, 36], and four studies compared a variety of physical fitness components, including agility, endurance, flexibility and speed [26, 27, 35, 36].…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic balance was measured using the berg balance scale [33], the timed up and go test [24, 25, 27, 28, 35], the 8 ft up and go test [29, 30, 34] and the walking in circle test [36]. Static balance was recorded with the Sharpened Romberg test [24, 28, 35] with both open and closed eyes, it was also registered by a Biodex Balance Stability System [32] and using a force platform where the subjects kept their arms on their hips to maintain position [36].…”
Section: Resultsmentioning
confidence: 99%
“…The WST is an important measure that correlates with functional capacity and dynamic balance, the potential of which is to predict functional decline as well as the risk of falls. 43 The strength of the LLs and the dynamic balance are directly related to the walking speed measured in the WST. 43 Bento et al 43 tested the balance of 65 women aged over 60 years, before and after a 12-week exercise protocol in water.…”
Section: Walking Speed Testmentioning
confidence: 99%
“…43 The strength of the LLs and the dynamic balance are directly related to the walking speed measured in the WST. 43 Bento et al 43 tested the balance of 65 women aged over 60 years, before and after a 12-week exercise protocol in water. The authors showed that the training in water had a positive effect on dynamic balance, allowing the study subjects to increase their walking speed.…”
Section: Walking Speed Testmentioning
confidence: 99%
“…Also, exercise interventions have implemented concurrent with breast neoplasms treatment could cause increase in cardiovascular fitness, muscular strength, and body composition and decrease in cancer-related fatigue ( 10 , 11 ). Various researchers have reported that water-based exercise is an ideal form of exercise for obese patients and might provide an attractive alternative to land-based exercise, to achieve improved health and fitness among these populations ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%